'The men who made the breakthrough': How the British press represented Patrick Steptoe and Robert Edwards in 1978. (June 2017) - Dow, Katharine
Abstract: This article examines how the British press represented Patrick Steptoe and Robert Edwards in the story of the birth of the first 'test-tube baby', Louise Brown. In 1978, the British press represented the birth of Louise Brown as both a success and a source of hope. The main pairs of protagonists in this story were Steptoe and Edwards and Lesley and John Brown, who metonymically represented British science and infertile couples, respectively. In the dominant 'success' narrative of the birth of Louise Brown as depicted in the British press in 1978, Edwards and Steptoe seemed to embody 'British' values of industriousness, perseverance, altruism, ingenuity and teamwork. Thus, their success was simultaneously a British success. With Louise Brown's birth, in-vitro fertilization came to stand for the potential happiness of infertile people and a bright future for British science and industry.